Efecto de los corticosteroides en la trasmisión congénita de toxoplasmosis experimental - Chinchilla, M (Universidad de Costa Rica, 1992)
Female white mice with chronictoxoplasmosis were treated with cortisone acetate (3mg for each 2S g of body weight) 12, 8, 4 and 0 days before mating. Cortisme induces congenital transmission of T. gondii